2004
DOI: 10.1152/ajprenal.00089.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein lipase in the kidney: activity varies widely among animal species

Abstract: Much evidence points to a relationship among kidney disease, lipoprotein metabolism, and the enzyme lipoprotein lipase (LPL), but there is little information on LPL in the kidney. The range of LPL activity in the kidney in five species differed by >500-fold. The highest activity was in mink, followed by mice, Chinese hamsters, and rats, whereas the activity was low in guinea pigs. In contrast, the ranges for LPL activities in heart and adipose tissue were less than six- and fourfold, respectively. The activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
3
18
1
Order By: Relevance
“…This enzyme is primarily expressed in tissues that use fatty acids for fuel or store large amounts of TGs, such as parenchymal cells of the adipose tissue, skeletal muscle, heart, and kidney cortex, and is secreted to the endothelium of local blood vessels (53). Previous studies by Olivecrona's group (46) demonstrated that LPL is present in mouse kidney proximal tubular epithelial cells; however, the regulation of LPL enzyme activity or its expression during acute kidney injury has not been previously examined. We found that similar to the effects of reducing epididymal white adipose tissue mass and LPL activity, cisplatin also inhibited the expression and enzyme activity of kidney LPL.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is primarily expressed in tissues that use fatty acids for fuel or store large amounts of TGs, such as parenchymal cells of the adipose tissue, skeletal muscle, heart, and kidney cortex, and is secreted to the endothelium of local blood vessels (53). Previous studies by Olivecrona's group (46) demonstrated that LPL is present in mouse kidney proximal tubular epithelial cells; however, the regulation of LPL enzyme activity or its expression during acute kidney injury has not been previously examined. We found that similar to the effects of reducing epididymal white adipose tissue mass and LPL activity, cisplatin also inhibited the expression and enzyme activity of kidney LPL.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the availability of apoC-I, apoC-II, apoC-III, and apoE, which are added to VLDL during assembly in the liver or are transferred to VLDL from HDL in the circulation, can affect the lipolytic activity [27,28,29,30,31], and a relative deficiency in apoC-II and increase in apoC-I and apoC-III has been reported in VLDL of subjects with CKD [31,32,33]. In addition, the kidney expresses both lipoprotein lipase and VLDL receptor [34,35]; therefore, CKD may affect the clearance of VLDL-TG and VLDL particles directly.…”
Section: Discussionmentioning
confidence: 99%
“…The specific immunolocalization with anti-LPL antibodies by using immunohistochemistry is expressed in the glomerular endothelial, parietal epithelial, and tubular epithelial cells, where ectopic lipid deposition is observed in HSFD-fed minipigs with Oil Red O staining. However, there are conflicting reports that LPL is expressed by different types of renal cells, and its mRNA, mass and activity in kidneys vary widely among different species, such as human, mink, mouse, rat and Chinese hamster [11,12,30-33]. Mesangial cells, but not epithelial cells, express LPL mRNA in human and rat [11].…”
Section: Discussionmentioning
confidence: 99%
“…Mesangial cells, but not epithelial cells, express LPL mRNA in human and rat [11]. Immunostaining for kidney LPL indicates that the enzyme is present in tubular epithelial cells of mouse and mink [12] and vascular endothelium of glomeruli in guinea pig [34]. To our knowledge, the present study is the first to report that the expression and activity of LPL are evaluated in the kidney of Chinese Bama minipigs, and down-regulated by HSFD for 5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation